2019
DOI: 10.1038/s41598-019-46877-3
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of a virtual reality counselling paradigm using embodied self-dialogue

Abstract: When faced with a personal problem people typically give better advice to others than to themselves. A previous study showed how it is possible to enact internal dialogue in virtual reality (VR) through participants alternately occupying two different virtual bodies – one representing themselves and the other Sigmund Freud. They could maintain a self-conversation by explaining their problem to the virtual Freud and then from the embodied perspective of Freud see and hear the explanation by their virtual doppel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 38 publications
0
59
0
1
Order By: Relevance
“…More recently, Banakou et al (2018) showed that embodying virtual Albert Einstein results in better performance on an executive functions task, as compared to embodying a normal-looking body, and also reduces implicit bias against the elderly, a result first observed in Yee and Bailenson (2006). Similarly, Osimo et al (2015) and Slater et al (2019) showed that when participants find themselves in the virtual body of Dr. Sigmund Freud, it helped them find a more satisfactory solution to a personal problem and positively influenced their mood compared to when they are embodied in a look-alike virtual body.…”
Section: Introductionmentioning
confidence: 93%
“…More recently, Banakou et al (2018) showed that embodying virtual Albert Einstein results in better performance on an executive functions task, as compared to embodying a normal-looking body, and also reduces implicit bias against the elderly, a result first observed in Yee and Bailenson (2006). Similarly, Osimo et al (2015) and Slater et al (2019) showed that when participants find themselves in the virtual body of Dr. Sigmund Freud, it helped them find a more satisfactory solution to a personal problem and positively influenced their mood compared to when they are embodied in a look-alike virtual body.…”
Section: Introductionmentioning
confidence: 93%
“…Another innovative approach involves allowing a single user to alternate between two virtual bodies (one being Sigmund Freud) engaged in a conversation, essentially a form of semi-externalized self-dialogue. Compared to a scripted control condition, participants engaged in embodied self-dialogue reported being helped and changed to a greater degree (Slater et al 2019). In addition to inspiring a new line of research, this type of paradigm presents a fine example of how a generic CBT technique like perspective-changing can be empowered and amplified using VR (Lindner et al 2019a).…”
Section: Embodimentmentioning
confidence: 99%
“…• Body swapping: The technique of body swapping in VR, where one person converses with themselves by successively occupying two different virtual bodies has thus far been used for positive means, such as solving personal problems, for example, people can alternately switch between describing a personal problem while embodying a virtual body closely resembling themselves, and offering themselves counseling while embodying a virtual representation of Dr. Sigmund Freud (Osimo et al, 2015;Slater et al, 2019). It is possibleif unlikely-that the same technology could be used to gain insight into another person's mind, insofar as the mind reflects in some sense the physical body, and thereby gain advantage.…”
Section: Identity Hackingmentioning
confidence: 99%